Supplying safe water in Bangladesh: A policy model based on multi-objective mixed integer programming - Akmam, Wardatul; Higano, Yoshiro (Papers in Regional Science, 2007)
.  At present, about 80 million people in Bangladesh are at risk of losing their health and having a sharply reduced life expectancy as a result of exposure to excessive arsenic through drinking water from tube wells. In this article, we build a multi‐objective mixed‐integer optimisation model, which we can simulate. We identify efficient loci of the trade‐off between the several competing objectives in order to provide safe water to the affected people. Three types of simulation cases are discussed. For each case, a different type of safe water was chosen as optimal.